Missing, presumed : a novel - Steiner, Susie, 1971- (Random House, 2016)
"Detective Manon Bradshaw is 39, single, and miserable as sin. She has endured some of the worst dates in internet history. But she loves her job and performs it brilliantly; all she needs to rise up in the ranks is a big break. Edith Hind is a gorgeous, intrepid graduate student at Cambridge University who seems to have it all: a doting boyfriend, a devoted friend named Helena, a loving mother and a father who is a surgeon to the Royal Family. When Edith turns up missing from her apartment one evening, leaving only a single streak of blood along the front foyer wall, the case becomes a national media sensation. In the first frenzied 72 hours of being assigned to the case, Bradshaw will make a number of alarming discoveries: Edith's behavior had been erratic in the run-up to her disappearance, and her close friend Helena, the last person to see her, is clearly hiding something. A known sex offender appears in CCTV footage of Edith taken a short while before she goes missing. Then a body is discovered floating in a nearby river. Is Edith Hind alive or dead? Was her "complex love life" at the heart of her disappearance, as the tabloids are suggesting? Why is there reluctance, in the senior ranks, to press too hard on some elements of the story? Detective Bradshaw must use all her skill and resources to bring closure to the case for Edith's family, as she finds herself becoming ever more personally, and dangerously, invested"--